Um olhar perspectivo sobre a(s) cultura(s) caipira(s) brasileira(s): reflexões a propósito da experiência de uma cidade do interior paulista - Humberto Perinelli Neto; Andréa Coelho Lastória; Rafael Cardoso De Mello (Caravelle)
This article presents the main aspects of caipira’s culture, putting the accent on bovine trade’s consequences upon urban spaces in Brazil’s Central Southern region, based on the historical experience of the town of Barreto, in the interior of São Paulo’s state. It also proposes some considerations concerning the way the elite has managed various expressions belonging to this culture during two precise periods : at the end of the 19th century and during the nationalistic wave which followed Getulio Vargas’s seizure of power in 1930.